Efektivitas Program Maghrib Mengaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an dan Menanamkan Nilai Religius pada Anak-Anak Desa Simangambat Tambangan - Miladiyah; Tuty Alawiyah Pohan; Sunanto Nauli; Sofiah; Saipul Mahya; Maulana Muklis; Laila Sakinah Siregar; Khoirunnisah Rangkuti; Afrina; Melda Diana Nasution (Sujud: Jurnal Agama, Sosial dan Budaya, 2025)
The Maghrib Mengaji program in Simangambat Tambangan Village plays a crucial role in maintaining the Qur'anic tradition within the community. This activity is held after sunset, specifically between sunset and Isha'. This program aims to improve children's understanding and skills in reading the Qur'an. In Simangambat Tambangan Village, there is great potential to develop this program, but challenges such as the lack of effective teaching methods, limited facilities, and the challenges of modernization often hinder the process of learning to recite the Qur'an and the formation of Qur'anic morals. To overcome these challenges, optimization strategies are needed, such as the implementation of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) as a complement to non-formal education, which also plays an important role in building the character and religious identity of the younger generation. With this additional program, it is hoped that children will be better prepared and more confident in learning to read the Qur'an properly and correctly. Furthermore, the community also needs to be involved in the planning and evaluation of the program to make it more relevant to their needs. With a collaborative approach and support from the Program Kuliah Kerja Nyata (KKN) STAIN MADINA, it is hoped that the Maghrib Mengaji (Quranic Study Group) activity will provide maximum benefits to the community and foster a love of the Quran among children, the nation's younger generation